Design and Development of IP for Modified Haar Wavelet Transform (MHWT) Image Fusion using FPGA - Sumant S Yaliagr; Sanket Dessai (International Journal of Reconfigurable and Embedded Systems (IJRES), 2018)
The fast growth in the field of digital imaging applications in remote sensing, bio medical and other satellite applications had created an architecture studies for image fusion in capable to store large amount of data and process. An algorithm considered for the process of image fusion for implementation of FPGA is Modified Haar Wavelet Transform (MHWT) based image fusion where at the time four pixels are consider in calculation of different bands as compared to conventional Haar wavelet based image fusion. The process of modification uses far less memory and computation power. The FPGA implementation of MHWT based image fusion is done on Digilent development board with Spartan 6 series FPGA. The architecture is developed in VHDL. The timing analysis is done and report is obtained for I/O interactions, memory units etc. The architecture is made to run in cosimulation with Simulink. The design is tested with different kinds of images and run successfully. The visual analysis of the resultant fused image is achived and observed.